J-aggregates of amphiphilic cyanine dyes: Self-organization of artificial light harvesting complexes - Stefan Kirstein; Siegfried Daehne (International Journal of Photoenergy)
The simultaneous chemical linkage of cyanine dye chromophores with both hydrophobic and hydrophilic substituents leads to a new type of amphiphilic molecules with the ability of spontaneous self-organization into highly ordered aggregates of various structures and morphologies. These aggregates carry the outstanding optical properties of J-aggregates, namely, efficient exciton coupling and fast exciton energy migration, which are essential for the build up of artificial light harvesting systems. The morphology of the aggregates depends sensitively on the molecular structure of the chemical substituents of the dye chromophore. Accordingly, lamellar ribbon-like structures, vesicles , tubes, and bundles of tubes are found depending on the dyes and the structure can further be altered by addition of surfactants, alcohols, or other additives. Altogether the tubular structure is the most noticeable structural motif of these types of J-aggregates. The optical spectra are characterized in general by a complex exciton spectrum which is composed of several electronic transitions. The spectrum is red-shifted as a total with respect to the monomer absorption and exhibits resonance fluorescence from the lowest energy transition. For the tubular structures, the optical spectra can be related to a structural model. Although the molecules itself are strictly achiral, a pronounced circular dichroism (CD) is observed for the tubular aggregates and explained by unequal distribution of left- and right-handed helicity of the tubes. Photo-induced electron transfer (PET) reactions from the dye aggregates to electron acceptor molecules lead to superquenching which proves the delocalization of the excitation. This property is used to synthesize metal nanoparticles on the aggregate surface by photo-induced reduction of metal ions.